The Role of Planning and Construction Factors in The Performance of Design and Build Contracts for The East Surabaya Hospital Project - Dicky Rianda Perdana; Andi Patriadi; Sajiyo Sajiyo (Journal of Social Science, 2025)
The construction industry plays a crucial role in developing infrastructure, including essential facilities like hospitals. In recent years, the design and build method has gained popularity due to its ability to integrate design and construction phases under a single contract, offering efficiency in both time and cost. However, alongside its advantages, this method brings numerous risks that can significantly affect project outcomes, especially in terms of completion delays. This research aims to analyze the influence of risk factors in design and build on the time performance of hospital construction projects. The design and build model is one of the most commonly used contract methods in construction projects due to its effectiveness in simplifying the implementation stages. However, the application of this method is often faced with risks that can affect project completion, particularly in time management. This study employed data collection techniques using questionnaires on planning and construction factors. The collected data were analyzed using Pearson correlation to determine the relationships between variables and multiple linear regression to measure the impact of risk factors on the project's time performance. The results show that construction factors have variables with significant and strong relationships to project success, while planning factors have some variables with weak and insignificant relationships. Therefore, risk management efforts should focus on variables with strong and significant correlations to ensure the project's optimal success.